2017
DOI: 10.1016/j.freeradbiomed.2016.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Hide and seek: How do DNA glycosylases locate oxidatively damaged DNA bases amidst a sea of undamaged bases?

Abstract: The first step of the base excision repair (BER) pathway responsible for removing oxidative DNA damage utilizes DNA glycosylases to find and remove the damaged DNA base. How glycosylases find the damaged base amidst a sea of undamaged bases has long been a question in the BER field. Single molecule total internal reflection fluorescence microscopy (SM TIRFM) experiments have allowed for an exciting look into this search mechanism and have found that DNA glycosylases scan along the DNA backbone in a bidirection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 87 publications
(77 reference statements)
0
36
0
Order By: Relevance
“…Moreover, recent studies suggest that some DNA glycosylases diffusively scan DNA using a ''wedge'' amino acid residue to identify damaged nucleotides. [16][17][18]32,[34][35][36][37] The function of the ''wedge'' amino acid is to sense damaged DNA bases before their eversion into the enzyme's active site. Because mutual conformational changes of the enzyme and DNA play an important role in the damage recognition and in the formation of a catalytic complex, in the present work, we performed a pre-steady-state kinetic analysis of protein-DNA interactions with fluorescent detection to resolve processes of conformational adjustments of DNA glycosylase and DNA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, recent studies suggest that some DNA glycosylases diffusively scan DNA using a ''wedge'' amino acid residue to identify damaged nucleotides. [16][17][18]32,[34][35][36][37] The function of the ''wedge'' amino acid is to sense damaged DNA bases before their eversion into the enzyme's active site. Because mutual conformational changes of the enzyme and DNA play an important role in the damage recognition and in the formation of a catalytic complex, in the present work, we performed a pre-steady-state kinetic analysis of protein-DNA interactions with fluorescent detection to resolve processes of conformational adjustments of DNA glycosylase and DNA.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, it was reported that DNA glycosylases with different structures and specificity have common structural features of DNA lesion recognition including insertion of ''wedge'' amino acids into DNA. 17,18,35,[54][55][56] Therefore, the movement of the intercalating loop is probably associated with the ''wedge'' strategy of hSMUG1 for DNA lesion search. At the second step, the intercalating loop of SMUG1 is completely inserted into the void in DNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that the etiology of BER-related syndromes and their dramatic effects on the nervous system probably stem from the high oxygen utilization of the brain that leads to frequent oxidative DNA lesions (1). In this regard, APE1 is key for suppressing the accumulation of oxidative DNA damage, being an essential factor in BER after both direct formation of AP sites and damaged base removal by one of several DNA glycosylases (7,9,81). The shift to mitochondrial respiration markedly impacts neonatal physiology, including the nervous system (82).…”
Section: Discussionmentioning
confidence: 87%
“…BER involves sequential steps in repairing base modifications. To initiate BER, DNA glycosylases recognize and remove different types of base damage, generating apurinic or apyrimidinic (AP) sites (8,9). AP sites can also be generated directly via spontaneous hydrolysis or through the action of ROS.…”
mentioning
confidence: 99%